Momentum Strategies: Evidence from Pacific Basin Stock Market - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2002)
We investigate the profitability of momentum investment strategy in six Asian stock markets. Unrestricted momentum investment strategies do not yield significant momentum profits. Although we find that a diversified country-neutral strategy generates small but statistically significant returns during 1981–1994, when we control for size and turnover effects we find that the country-neutral profits dissipate. Our evidence suggests that the factors that contribute to the momentum phenomenon in the United States are not prevalent in the Asian markets.